Examining the impact of NAMA Foundation’s BRIGHT program on students’ sense of efficacy in Indonesia, Kyrgyzstan, and Tanzania - Kassim, Siti Kholijah; Ssekamanya, Siraje Abdallah; Khalid, Nursyahidah; Megat Ramli, Puteri Azlian (IIMU, 2025)
This study examines the impact of the NAMA Foundation’s BRIGHT program on secondary students’ sense of efficacy in Indonesia, Kyrgyzstan, and Tanzania. Employing a longitudinal, quantitative design, the research compared baseline data from 2021 with midterm data from 2022, analyzing responses from 1,728 students in 63 participating schools. The Student Questionnaire, validated for reliability and convergent validity, measured the sense of efficacy across ten domains, including problem-solving, achievement, self-expression, and advocacy. Principal components analysis and independent t-tests revealed significant improvements in overall efficacy scores following the intervention, with most items showing large effect sizes. However, the gains in advocacy and assertiveness were notably smaller for Tanzanian students, suggesting contextual barriers. The findings affirm previous literature highlighting the link between holistic interventions and positive psychosocial outcomes, and they extend this knowledge to under-researched, low- and middle-income countries. This study underscores the value of structured, context-sensitive educational programs for enhancing students’ confidence, agency, and school engagement. The results offer important implications for policymakers, educators, and international agencies aiming to foster holistic student growth in diverse, resource-constrained settings